Study of the Irradiation effect on the optical properties for the SnO2 thin film - Kasim H. mahmood (Tikrit Journal of Pure Science)
In this report investor the optical properties of the thin film SnO2 , before and after Irradiation by Argon Laser Ar+. We found same varieties has been achieve on optical properties of a thin film SnO2.